Servant Leadership: Sebuah Strategi Inovatif Manajemen Pendidikan Kristen - Justice Zeni Zeni Zari Panggabean (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to explore innovative strategies in Christian education management implemented through a servant leadership approach to educate a generation of faith and integrity. The servant leadership approach emphasizes servant leadership, where the leader focuses on the needs of others and inspires them to reach their maximum potential. This study uses qualitative methods with case study analysis in several Christian educational institutions. The research results show that the application of innovative strategies based on servant leadership is able to increase student motivation and involvement, strengthen spiritual values, and form characters with integrity. Implementation of this strategy involves holistic curriculum development, training and professional development for educators, as well as active participation from the school community. In conclusion, Christian education management that adopts servant leadership principles can effectively educate the younger generation who not only excel academically but also have strong faith and high integrity. Keyword: Christianity, Education, Innovative, Management, Servant Leadership, Strategy